Ask Question
4 September, 23:13

Solve for f.

-11f = 7 (1 - 2f) + 5

f=

+3
Answers (1)
  1. 5 September, 00:41
    0
    f = 4

    Step-by-step explanation:

    We start by re organizing the equation so all the numbers and variables that includes f, goes to the left side of the equation, while the rest of the numbers go to the right.

    -11f = 7 - 14f + 5

    -11f + 14f = 7 + 5

    3f = 12

    f = 4

    I hope you get this now : ] If you need any more clarification, feel free to ask me!
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Solve for f. -11f = 7 (1 - 2f) + 5 f= ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers